Kecernaan Nutrien dan Energi Metabolis Semu Ayam Broiler Yang Disuplementasi Nukleotida Pada Suhu Lingkungan Berbeda - A. F. Rusydy; L. D. Mahfudz; Maulana Hamonangan Nasution (Universitas Bengkulu, 2022)
This study examined the effect of nucleotide supplementation in broiler feeds reared at different environmental temperatures on nutrient digestibility and apparent metabolizable energy. This research used 135 unsexed broilers at 15 days old with an average body weight of 462.20 ± 9 g and nucleotide supplement. This research used a completely randomized design (CRD) in a factorial pattern of 3 X 3 with five replications. The treatments given were nucleotide levels, N0 (0 g/kg feed), N1 (0.5 g/kg feed), N2 (1 g/kg feed), and environmental temperatures, S1 (heat 32±1°C), S2 (comfortable 23±1°C) and S3 (natural 24-34°C). The parameters measured were nutrient consumption, fat digestibility, protein digestibility, and apparent metabolizable energy. Data were analyzed by analysis of variance (ANOVA) with the F test at 5% and continued with Duncan's Multiple Range test. The results showed no interaction (P>0.05) between nucleotide levels with different environmental temperatures on nutrient consumption, fat digestibility, protein digestibility, energy consumption, and apparent metabolizable energy. Heat temperature decreased (P<0.05), as it was in fat, protein, and energy consumption. Supplementation of nucleotide 1 g / kg decreased (P<0.05) protein digestibility, energy consumption, and apparent metabolizable energy. It was concluded that supplementing 1g / kg of nucleotide increased broilers' protein efficiency and energy use.